2002
DOI: 10.1093/humrep/17.7.1906
|View full text |Cite
|
Sign up to set email alerts
|

Salivary progesterone levels and rate of ovulation are significantly lower in poorer than in better-off urban-dwelling Bolivian women

Abstract: Progesterone levels appear to be influenced by chronic and acute ecological conditions, evidenced by the association with body-size and the probability of ovulation respectively. These findings have implications for understanding cancer aetiology, developing population-appropriate hormonal contraceptives, and modelling the evolution and functioning of the reproductive system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 20 publications
2
55
1
Order By: Relevance
“…Ovarian cycle length in rural Aymara women averaged 29.1 days, which falls within the observed range for sea level [ 13 ]. The proportion of ovulatory cycles, as assessed by progesterone levels, was comparable in a sample of Chicago women and economically advantaged women in La Paz, Bolivia (91 % and 88 % respectively); however, it was far lower (45 %) in the poorer women of La Paz [ 14 ]. Mean progesterone levels in ovulatory cycles among poor women were lower than those in better off peers and substantially lower than in Chicago women.…”
Section: Fertilitysupporting
confidence: 62%
“…Ovarian cycle length in rural Aymara women averaged 29.1 days, which falls within the observed range for sea level [ 13 ]. The proportion of ovulatory cycles, as assessed by progesterone levels, was comparable in a sample of Chicago women and economically advantaged women in La Paz, Bolivia (91 % and 88 % respectively); however, it was far lower (45 %) in the poorer women of La Paz [ 14 ]. Mean progesterone levels in ovulatory cycles among poor women were lower than those in better off peers and substantially lower than in Chicago women.…”
Section: Fertilitysupporting
confidence: 62%
“…Within populations, midluteal progesterone in ovulatory cycles is positively correlated with stature in Bolivian women (10). In U.S. women, associations of measures of body size and levels of hormones and sex-hormone-binding globulin have also been observed (22,23).…”
Section: Figmentioning
confidence: 94%
“…In U.S. women, relatively lower progesterone is associated with subfecundity among patients at infertility clinics, perhaps signaling failure to ovulate or luteal insufficiency (7), and is also associated with a reduction in risk of conception (8). Yet studies of women from nonindustrialized populations have consistently observed progesterone levels averaging only about two-thirds of the average levels of U.S. women (9)(10)(11)(12)(13). Does the typically much lower progesterone observed among women in nonindustrialized populations signal a significant impairment of reproductive function relative to U.S. women?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because saliva can be readily collected from subjects on multiple occasions, it is possible to compare steroid levels across entire menstrual cycles among different women rather than relying on one or a few timed blood samples. Salivary levels of ovarian steroids have been used by many investigators to demonstrate adaptive shifts in ovarian function under conditions of energy constraint in adult women (15,(19)(20)(21)(22)(23)(24)(25)(26)(27). Salivary estradiol (E2) levels are particularly sensitive indicators, with a shift to lower levels being associated with energy constraint and lower probability of conception (18).…”
mentioning
confidence: 99%